Comparison of different control strategies on a vehicle using sliding mode control - Guclu, R; Yagiz, N (SHIRAZ UNIV, 2004)
In this study, the vibration control of a half vehicle model with a passenger seat using a sliding mode control is considered. Three cases are taken into account as the control strategies. First, the model having passive suspensions with an active passenger seat is studied. Then active suspensions and passive seat combination is examined. In the last case, both the passenger seat and suspensions are active. Pitch motions of the vehicle body and bounce motions of the passenger in the three cases due to road input, which is a commonly used speed bump to slow down the vehicles at junctions in some countries, are simulated and the results are compared in order to select the combination which provides the best ride comfort.
Keywords: active passenger seat; active suspensions; control strategy; sliding mode control; PERFORMANCE; SYSTEM; SEAT; Science & Technology - Other Topics